Current-Voltage Analysis of PCBM:PCDTBT Blend To Find Out Charge Transport Path - Saatci, A. Evrim; Kavak, Pelin; Parlak, Elif Alturk; Gokdemir, F. Pinar; Menda, U. Deneb; Ozdemir, Orhan; Kutlu, Kubilay (AMER INST PHYSICS, 2013)
Transport path(s) of charge carrier were identified through I-V measurement within the structure of ITO/PEDOT:PSS/PCDTBT:PCBM/TiOx/Ca/Ag in which ohmic regime was enrolled in low bias side while space charge limited conduction mechanism governed at high bias side. Moreover, influence of each constitituent parts of the present device on the dc transport properties was investigated by preparing ITO/PEDOT:PSS/PCDTBT/Ca/Ag and ITO/PEDOT:PSS/ PCBM/Ca/Ag structures and repeating the mentioned experimental techniques.
Keywords: Organic solar cell; charge transport path(s); SOLAR-CELLS; Materials Science; Physics